Identification of the role of oral health educators in elementary schools during COVID-19 pandemic: a competency framework - Adel Khiami; Mayssoon Dashash (BMC Research Notes, 2022)
Abstract Objective Oral health educators should have the required knowledge, skills and attitude in order to meet the increased needs of the Ministry of Education in Syria as well as to perform their duties in promoting oral health in children appropriately during the COVID-19 pandemic. Therefore, this study was undertaken to identify core competencies required for oral health educators in elementary schools during the COVID-19 pandemic. Qualitative exploratory study was undertaken. A focus group which consisted of 5 Medical Education postgraduates and 3 oral health educators’ training team members were invited to formulate a preliminary list of basic competencies. Delphi technique was also adopted through inviting 12 experts in oral health education to evaluate and formulate a final list of elementary schools’ oral health educators’ competencies during the COVID-19 pandemic. Results A competency framework was developed. Fifty-five competencies were identified including 35 in cognitive domain, 12 skills and 8 attitude competencies. A list of essential competencies has been identified. These competencies should be addressed in training programs targeting oral health educators, which can consequently produce competent educators who can successfully promote and provide health care to all schoolchildren during the COVID-19 pandemic.